2011
DOI: 10.1136/hrt.2010.213579
|View full text |Cite
|
Sign up to set email alerts
|

Generalised muscle weakness in young adults with congenital heart disease

Abstract: Respiratory and skeletal muscle weakness is common in young adults with complex CHD and similar to that found in older adults with advanced heart failure from acquired heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 29 publications
9
72
2
Order By: Relevance
“…There is evidence that adults with CHD are deconditioned as a result of inappropriate restriction from participation in physical activities. 36 -38 In fact, Greutmann et al 39 recently showed that the degree of respiratory and skeletal muscle weakness commonly present in adult CHD patients is comparable to that in patients with advanced heart failure in acquired heart disease. It is possible that patients with muscle weakness terminate CPX before the limits of the cardiovascular system are reached, which, in turn, would result in failure to achieve VT.…”
Section: Inuzuka Et Al Exercise Testing In Congenital Heart Diseasementioning
confidence: 99%
“…There is evidence that adults with CHD are deconditioned as a result of inappropriate restriction from participation in physical activities. 36 -38 In fact, Greutmann et al 39 recently showed that the degree of respiratory and skeletal muscle weakness commonly present in adult CHD patients is comparable to that in patients with advanced heart failure in acquired heart disease. It is possible that patients with muscle weakness terminate CPX before the limits of the cardiovascular system are reached, which, in turn, would result in failure to achieve VT.…”
Section: Inuzuka Et Al Exercise Testing In Congenital Heart Diseasementioning
confidence: 99%
“…Respiratory and skeletal muscle weakness was common in young adults with complex CHD and similar to that found in adults with advanced heart failure from acquired disease. 69 Intrinsic causes of restrictive lung disease include decreased pulmonary blood flow that may hinder growth and development of lung parenchyma, resulting in pulmonary hypoplasia. 70 This may partly explain the significantly higher prevalence of restrictive lung physiology in patients with TOF.…”
Section: Pathogenesismentioning
confidence: 99%
“…Skeletal muscle atrophy and weakness accompany several pathophysiological conditions, including muscle disuse (D'Antona et al, 2003), aging (Gosselin et al, 1994;Larsson et al, 1997a;Larsson et al, 1997b;Lowe et al, 2001;Thompson and Brown, 1999), cancer (Roberts et al, 2013a;Roberts et al, 2013b) and chronic heart failure (Evans et al, 1995;Greutmann et al, 2011). The loss of skeletal muscle mass and impaired function during these conditions contribute to reduced physical performance and quality of life, prolonged hospital stays and enhanced mortality (Evans, 2010).…”
Section: Introductionmentioning
confidence: 99%